“In-Group” Communication in Marine Vibrio: A Review of N-Acyl Homoserine Lactones-Driven Quorum Sensing - Liu, Jianfei; Fu, Kaifei; Wu, Chenglin; Qin, Kewei; Li, Fei; Zhou, Lijun (Frontiers in Cellular and Infection Microbiology, 2018)
N-Acyl Homoserine Lactones (N-AHLs) are an important group of small quorum-sensing molecules generated and released into the surroundings by Gram-negative bacteria. N-AHLs play a crucial role in various infection-related biological processes of marine Vibrio species, including survival, colonization, invasion and pathogenesis. With the increasing problem of antibiotic abuse and subsequently the emergence of drug-resistant bacteria, studies on AHLs are therefore expected to bring potential new breakthroughs for the prevention and treatment of Vibrio infections. This article starts from AHLs generation in marine Vibrio, and then discusses the advantages, disadvantages, and trends in the future development of various detection methods for AHLs characterization. In addition to a detailed classification of the various marine Vibrio-derived AHL types that have been reported over the years, the regulatory mechanisms of AHLs and their roles in marine Vibrio biofilms, pathogenicity and interaction with host cells are also highlighted. Intervention measures for AHLs in different stages are systematically reviewed, and the prospects of their future development and application are examined.